Influence of Landing Net Mesh Type on Handling Time and Tissue Damage of Angled Brook Trout. (29th March 2018) - Lizée, Teah W.; Lennox, Robert J.; Ward, Taylor D.; Brownscombe, Jacob W.; Chapman, Jacqueline M.; Danylchuk, Andy J.; Nowell, Liane B.; Cooke, Steven J.
Abstract: Recreational catch‐and‐release angling is a popular activity. Anglers often use landing nets to shorten fight times, reduce stress on the line and rod, restrict fish movement to facilitate dehooking of the fish, and protect fish from undue harm caused by handling or dropping. Landing nets are constructed using a variety of netting materials that could have varied consequences when coming in contact with fish. Salmonids are among the most targeted fishes in the world, but little is known about how landing nets contribute to postcapture tissue damage. We compared handling time and instances of fin fraying, scale loss, and mucus loss sustained by Brook Trout Salvelinus fontinalis landed by four net mesh types (i.e., large, knotless rubber mesh; knotless nylon micromesh; large, knotted polypropylene mesh; and small, knotless rubber‐coated nylon mesh) or by using bare wet hands in a recreational fishery. The knotted polypropylene mesh resulted in the greatest extent of fin fraying, whereas the bare wet hands method, knotless nylon micromesh, and rubber‐coated nylon mesh resulted in the most scale loss. Interestingly, extended handling times were noted for several mesh types (i.e., knotless nylon micromesh and rubber‐coated nylon mesh) relative to bare wet hands because of hook entanglement in the netting material. However, using bare wet hands to land Brook Trout resulted in higher odds of the fish being dropped into the bottom of the boat. We concluded that the large, knotless rubber mesh was the least damaging to Brook Trout. Changes to angler practices, such as using appropriate landing tools, can benefit fish welfare in catch‐and‐release fisheries.